Fibre bleaching with hydrogen peroxide and percentage of medullation in black and brown Huacaya alpaca - Lozano, Franklin (2023)
The aim of this study was to determine the bleaching time of the black and brown fibre with hydrogen peroxide and to evaluate the percentage of medullated fibres according to colour and sampling site in the Huacaya alpaca fleece. In total, 90 fibre samples (shoulder, mid-side area, and rump) were taken from 30 alpacas (10 black, 10 brown, and 10 white). The fibre (2 g) was bleached at different times (5-105 min) with 20 g hydrogen peroxide (40 volume oxygenated cream) and 10 g bleaching powder (High lift 9 Tones). The colorimetric coordinates (L*a*b*) were evaluated at 5, 10, 35, 70 and 105 min in black fibre and at 35 and 70 minutes in brown fibre. After the microscopic analysis, fibre medullation percentage and their standard error were calculated. The luminosity in black fibre is low (5.19 ± 1.78), which increases with bleaching time to 86.60 ± 1.49 at minute 105. The luminosity in brown fibre is greater (43.18 ± 10.47) which increases to 86.92 ± 1.50 at minute 70. The luminosity of the bleached fibres in those times was similar to 87.14±1.43 of white fibre (standard reference). Fragmented medullation was the most common (38.54 ± 1.98, 31.56± 1.87%), followed by discontinuous (18.77 ± 1.58, 20.44 ± 1.62%), continuous (17.43 ± 1.53, 19.28 ± 1.58%), with few strongly medullated fibres (1.05 ± 0.4, 1.27 ± 0.45%) in black and brown alpacas, respectively. The percentage of medullated fibres in black alpaca (75.81 ± 1.72%) was similar to that of brown alpaca (72.55 ± 1.78%). These alpacas show a high percentage of medullation compared to the white one (50.77 ± 1.97%). The percentage of medulation did not show variation by fleece sampling site. The mean diameter of the black fibre was thicker than the white, but there were no differences between the black and white fibres. In conclusion, hydrogen peroxide is a bleaching agent that requires between 60 and 100 minutes for efficient bleaching of brown and black fibre, respectively. The black and brown fibres showed lower textile quality with a high percentage of medullation compared to the white fibre.